Effects of soy milk ingestion immediately after resistance training on muscular-related biomarkers in older males: a randomized controlled trial - Hooshmand-Moghadam, Babak; Johne, Monika; Golestani, Fateme; Lorenz, Katarzyna; Asad, Monireh; Maculewicz, Ewelina; Mastalerz, Andrzej (Biology of Sport, 2023)
We evaluated the effects of soy milk ingestion on changes in body composition, strength, power, and muscular-related biomarkers following 12 weeks of resistance training in older men. Thirty healthy older men (age = 65.63±  3.16 years; body mass = 62.63±3.86kg) were randomly assigned to one of two groups: soy milk + resistance training (SR) or placebo + resistance training (PR). Participants in the SR group received 240 ml of vanilla-flavoured non-dairy soy milk immediately after every training session and at the same time on non-training days. Differencesin muscle mass, upper limb body strength (UBS), lower limb aerobic power (LAP), activin A, and GDF15 were significantly greater in the SR group vs. the PR group (P < 0.05). Both intervention groups experienced a significant (p < 0.05) reduction in body mass (PR = -3.9 kg; SR = -3.2 kg), body fat % (PR = -0.8%; SR = -1.2%), activin A (PR = -5.1 pg/ml; SR = -12.8 pg/ml), GDF15 (PR = -8.1 pg/ml; SR = -14.7 pg/ml), TGFβ1 (PR = -0.43 pg/ml; SR = -0.41 pg/ml), and increase in muscle mass (PR = 0.81 kg; SR = 2.5 kg), UBS (PR = 3.4 kg; SR = 6.7 kg), lower limb body strength (PR = 2.8 kg; SR = 5.2 kg), upper limb aerobic power (PR = 34.3 W; SR = 38.6 W), LAP (PR = 23.2 W; SR = 45.2 W), BDNF (PR = 8.3 ng/ml; SR = 12.7 ng/ml), and irisin (PR = 1.5 ng/ml; SR = 2.9 ng/ml) compared to baseline. The ingestion of soy milk during 12 weeks of resistance training augmented lean mass, strength, and power, and altered serum concentrations of skeletal muscle regulatory markers in older men.